Upaya Peningkatan Kebersihan Lingkungan Melalui Gotong Royong Bersama Masyarakat Dan Penyediaan Sarana Tempat Sampah Di RT 04 Anggut Bawah - Aprianty, Riska Eka; Sella, Paskah Tiara; Yoga, Waskita Martarabi; Saputra, Winki Herliansa; Jusmadi, Evryeni; Martiani, Martiani; Dianthi, Martha Heriniazwi (Jurnal Gotong Royong, 2026)
Environmental cleanliness is one of the important factors in creating a healthy and comfortable quality of life for the community. Waste problems that are still frequently found in residential areas are caused by low public awareness and limited supporting facilities, such as waste bins. This study aims to examine efforts to improve environmental cleanliness through community-based mutual cooperation activities and the provision of waste disposal facilities. The method used was a participatory approach by involving the community in collective cleaning activities and observing environmental conditions before and after the implementation of the program. The results indicate that regular mutual cooperation activities and the availability of adequate waste bins can increase public awareness of the importance of environmental cleanliness and reduce the amount of scattered waste. Furthermore, active community participation plays a significant role in maintaining the sustainability of environmental cleanliness. This study concludes that collaboration with the community, supported by adequate facilities and infrastructure, can be an effective strategy for improving environmental cleanliness.